Water problem and its implications for sustainable development - Al-Malki, Wael Mohammed; Al-Shamsan, Saleh Ibrahim; Al-Alewi, Abdulmalek Faisal; Al-Shebil, Mansour Abdullah; Al-Naser, Issam Suleiman (Journal of Economic, Administrative and Legal Sciences, 2024)
This study addresses water scarcity and its implications for sustainable development with a focus on identifying the challenges, negative impacts, and potential solutions to this global problem. The primary objective is to evaluate how water scarcity affects various dimensions of sustainable development, including economic, social, and environmental aspects, and to propose effective water management practices that mitigate these impacts. Employing a descriptive research approach, data were collected in 2024 from a randomly selected sample of 60 employees. A comprehensive questionnaire was utilized as the primary data collection tool, allowing for the gathering of detailed information on water usage, availability, and the perceived impact of water scarcity on their work and lives. The collected data were then analyzed using SPSS software to uncover patterns and discrepancies between water availability and consumption. The analysis revealed significant disparities between the amount of water available and the levels of consumption, leading to a range of economic, social, and environmental consequences. Economically, water scarcity was found to hinder industrial productivity and agricultural output, leading to increased costs and reduced economic growth. Socially, it exacerbated inequalities and heightened the risk of conflicts over water resources. Environmentally, water scarcity contributed to ecosystem degradation and loss of biodiversity, further threatening the sustainability of natural resources. Based on these findings, the study recommends the implementation of robust legislative frameworks, policies, and regulations that promote sustainable water management practices.